2015
DOI: 10.1182/blood-2014-09-599852
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic and acute anemia and extracranial internal carotid stenosis are risk factors for silent cerebral infarcts in sickle cell anemia

Abstract: Key Points• Baseline hemoglobin levels lower than 7 g/dL, acute anemia, and extracranial internal carotid stenosis are significant and independent risk factors for SCI in SCA.Early transcranial Doppler (TCD) screening of the Créteil sickle cell anemia (SCA)-newborn cohort, and rapid initiation of transfusion programs, resulted in successful prevention of overt strokes, but a high cumulative risk of silent cerebral infarcts (SCI) remained, suggesting that TCD screening does not identify all patients with SCA at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
160
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 41 publications
6
160
2
1
Order By: Relevance
“…The prevalence of WMCs in our cohort of adults (49%) was higher than that reported for cohorts of children, 8,15,20,[24][25][26][27] but it was highly consistent with the findings of a recent study reporting a prevalence of silent infarcts of 53% in a cohort of adult patients with SCD with a median age of 30 years. 28 However, caution is required when studies are compared directly because of differences among studies in definitions; brain imaging techniques; and population characteristics, particularly concerning cerebrovascular history.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The prevalence of WMCs in our cohort of adults (49%) was higher than that reported for cohorts of children, 8,15,20,[24][25][26][27] but it was highly consistent with the findings of a recent study reporting a prevalence of silent infarcts of 53% in a cohort of adult patients with SCD with a median age of 30 years. 28 However, caution is required when studies are compared directly because of differences among studies in definitions; brain imaging techniques; and population characteristics, particularly concerning cerebrovascular history.…”
Section: Discussionsupporting
confidence: 68%
“…28 However, caution is required when studies are compared directly because of differences among studies in definitions; brain imaging techniques; and population characteristics, particularly concerning cerebrovascular history. A steady increase in the prevalence of brain lesions with age was clearly demonstrated in children, in a recent study by Bernaudin et al 24 The cumulative risk of silent cerebral infarcts was found to increase from 19.2% at age 8 years, to 32.4% at age 14 years and 39.1% at age 18 years. In our study, the most common location of WMCs was the frontal area, and half of the patients had focal lesions only, which were consistent with findings with pediatric cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of SCI is complex and likely multifactorial (Debaun, Derdeyn, & McKinstry, 2006;Dowling, Quinn, Rogers, & Buchanan, 2010), but recent research has proposed a strong association with tissue-level hypoperfusion (Bernaudin et al, 2015). As such, the lack of relationship between SCI and TCD measurements potentially arises from an inability to detect changes in tissue-level cerebral blood flow (CBF) using TCD measures of BFV MCA .…”
Section: Tcd Furthermore Results From the Silent Cerebral Infarct Tmentioning
confidence: 99%
“…1 SCIs refer to permanent brain lesions, usually small, that do not produce obvious focal neurologic deficits. These smaller strokes are often not "silent" and can cause neurocognitive impairment and poor academic performance, as well as portend overt stroke.…”
Section: University Of Texas Southwestern Medical Centermentioning
confidence: 99%
“…Bernaudin et al hypothesized that common clinical complications associated with hypoperfusion and hypoxemia, such as AAEs and acute chest syndrome, as well as extracranial ICA stenosis, were associated with SCIs. 1 Recall, the risk for overt stroke is routinely assessed in SCA by ultrasonography of intracranial arteries. The study population was a contemporary (1992-2010) and aggressively treated cohort of children with SCA followed longitudinally by magnetic resonance imaging and angiography.…”
Section: University Of Texas Southwestern Medical Centermentioning
confidence: 99%